Gesundheit & Bewegung - Carlsohn A (Dynamic Media Sales Verlag, 2016)
For elite athletes, recovery from exhausting exercise is important during training and competitions. The effects of protein supplements on exercise-induced muscle damage, muscle soreness and restoration of muscle function or performance during recovery from strenuous exercises are not well established. Recently, some weak evidence has been found that post-exercise ingestion of protein, amino acids or milk may reduce muscle damage, muscle soreness and promote restoration of performance in or endurance sports (cycling, running).Following eccentric endurance exercises, protein supplementation has no effect on the above mentioned parameters. In trained athletes, muscle damage and soreness are not influenced by protein supplementation following resistance type exercise. However, there is some evidence that restoration of performance may be hastened by protein ingestion.KEY WORDS: Protein, Recovery, Muscle Soreness, Muscle Damage, Performance, Nutrition